Depositional framework of the Sangkarewang and Sawahlunto Formations, Ombilin Basin, West Sumatra, Indonesia - Zonneveld, J-P. (2025)
Analyses of rock samples collected during recent fieldwork in the Ombilin Basin of west-central Sumatra, Indonesia yielded pollen data that constrain the age and depositional setting of associated plant macrofossil and vertebrate fossil-bearing units in the Sangkarewang and Sawahlunto formations. Articulated fish and plant fossils were recovered from bedding plane surfaces of fissile, laminated shales in the Sangkarewang Formation that are interpreted to have been deposited in an actively-subsiding, deep, anoxic lake. The overlying Talawi Member of the Sawahlunto Formation records stratigraphy consistent with deposition in a segue to marginal lacustrine marsh and poorly-drained paleosol settings. Interbedded carbonate mudstone / wackestone and lignitic claystone units in the basal Talawi Member preserve scattered, disarticulated fossils of fish, reptiles, an amphibian, and one mammal tooth. These beds grade into a heterolithic succession of fine-grained clastic rock, with coal interbeds likely deposited in a coastal alluvial setting. Marine influences in this interval are indicated by the nature of physical sedimentary structures in several zones, the presence of trace fossils such as Diplocraterion, Cylindrichnus and Teichichnus, and the occurrence of foraminiferal linings, dinocysts and other palynomorphs indicative of mangrove and back-mangrove settings. Palynological analysis indicates that the most probable age of the Sawahlunto Formation ranges from the middle to late Eocene, with a possible extension from the middle Eocene to the early Oligocene.